Qualidade da informaç\~ao sobre recursos federais alocados por emendas parlamentares à saúde (2014-2024) - Filipe Matheus Silva Cavalcanti; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The allocation of federal resources through parliamentary amendments (PAs) to health increased between 2014 and 2024 due to the establishment of the mandatory budget for amendments, as well as the expansion of the execution of non-mandatory amendments. Given the significant participation of PAs in financing expenditures on Public Health Actions and Services (PHAS) and considering the role of the Federal Government in using resource transfers to states, the Federal District, and municipalities as a mechanism to reduce health inequalities in Brazil, it is necessary to conduct studies to investigate whether this goal is being achieved. However, for this, high-quality information on PA allocations is required. In this context, the aim of this study is to identify the main sources on health PAs and analyze the information quality. Publicly accessible information sources were mapped, and the quality of the obtained data was evaluated considering the following dimensions: accessibility (ease of obtaining), methodological clarity (existence of documentation and non-ambiguity of the criteria used in data production), coverage (extent of available databases), and consistency (reliability of the information). The results indicate that the lack of transparency in the allocation of federal resources through PAs remains a significant issue in Brazil, due to problems related to all the analyzed dimensions.
Keywords: H51; 330; health expenditures; budgets; information quality; parliamentary amendments; health care rationing; federal government; Unified Health System